PENGARUH PROFESIONALISME, GENDER DAN KOMPLEKSITAS TUGAS TERHADAP AUDIT JUDGMENT AUDITOR INTERNAL PADA SATUAN PENGAWAS INTERNAL PERGURUAN TINGGI DI SUMATERA : KONFLIK PERAN SEBAGAI VARIABEL MODERASI - Atika Faizah; Vince Ratnawati; Susilatri ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This study aims to look effect of professionalism, gender and complexity task of auditors judgment of internal audit in internal control unit of higher education in sumatra with role conflict as a moderating variable. The research was conducted on the Internal Audit Unit of the few universities in Sumatra This study time for 3 months commencing at the time of execution of this thesis. The population in this study is an internal auditor at the College in Sumatra. The sample in this study were all located on the Internal Auditor College in Sumatra. This study used a questionnaire as a primary data. Methods of data analysis used in this research is to use a simple linear regression based on the functional relationship or causal one independent variable with the dependent variable. The results of the study explained that the professionalism variables affect the judgment while the gender audit and the complexity of the task has no effect on audit judgment. And conflicting roles only able to moderate the influence of professionalism to the audit judgment, while gender and the complexity of the task is not able to moderate influence on audit judgment. In this study, there are still many limitatios and short comings the effect of independent variables on thedependent variable can only explain by 86,3%, hence more independent variable are needed.Keywords: Professionalism, Gender, Complexity And Audit Judgment